Regional Railway Transport in Czech, Austrian and German Decentralised and Regionalised Transport Markets - Daniel Seidenglanz; Tomáš Nigrin; Jiří Dujka (Review of Economic Perspectives, 2015)
The article analyses railway transport markets in three neighbouring Central European countries: the Czech Republic, Austria and Germany (specifically Bavaria and Saxony), with a focus on regional transportation. It examines the organisational form of public transport resulting from regionalisation and provides comparative case studies of regional train services in these countries. The article points out the organisational differences in public transportation between the studied regions and tries to connect these results with the supply of regional train services on various types of lines and in different geographical areas.
Keywords: 330